Evolusi Konsep Pemasaran Relasional dalam Manajemen Modern: Tinjauan Sistematis Literatur 2015–2025 - Juni Mashita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to systematically examine the evolution of relationship marketing within the scope of modern management over the period 2015–2025. Using a Systematic Literature Review (SLR) approach, this research analyzed scholarly articles from databases such as Scopus, Google Scholar, and ScienceDirect, based on inclusion criteria covering journal articles, proceedings, and relevant dissertations in both Indonesian and English. The findings reveal that relationship marketing has evolved from traditional personal interaction into a more digital, analytical, and context-based approach. Five core dimensions consistently emerge: trust, commitment, customer satisfaction, customer loyalty, and engagement. The study also highlights varied implementation approaches across industries and identifies several driving (technology adoption, consumer behavior) and inhibiting factors (organizational limitations, digital gaps). This review identifies critical research gaps, including a lack of longitudinal studies, limited focus on SMEs and developing countries, and minimal integration with artificial intelligence and big data. The practical implications emphasize the need for adaptive, data-driven relationship marketing strategies, while the theoretical contribution lies in the opportunity to develop new frameworks aligned with digital transformation. The study concludes with recommendations for future research, particularly empirical and longitudinal studies in underexplored sectors and contexts.